Field reports form for submitting seasonal observations of Iowa birds, Mark Proescholdt, fall 1993 - Proescholdt, Market al (1993)
Fall report of birds and locations contributed by Mark Proescholdt. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed